Mechanism Regulating Self-Intercalation in Layered Materials - Zhang, Peikun; Xue, Minmin; Chen, Changfeng; Guo, Wanlin; Zhang, Zhuhua (Nano letters, 2023)
Recent experimental breakthrough demonstrated a powerful synthesis approach for intercalating the van der Waals gap of layered materials to achieve property modulation, thereby opening an avenue for exploring new physics and devising novel applications, but the mechanism governing intercalant assembly patterns and properties remains unclear. Based on extensive structural search and energetics analysis by ab initio calculations, we reveal a Sabatier-like principle that dictates spatial arrangement of self-intercalated atoms in transition metal dichalcogenides. We further construct a robust descriptor quantifying that strong intercalant-host interactions favor a monodispersing phase of intercalated atoms that may exhibit ferromagnetism, while weak interactions lead to a trimer phase with attenuated or quenched magnetism, which further evolves into tetramer and hexagonal phases at increasing intercalant density. These findings elucidate the mechanism underpinning experimental observations and paves the way for rational design and precise control of self-intercalation in layered materials.